Static stretch versus Mulligan Concept - long-term effects in gymnast's flexibility - Manuela Karloh; Raquel Petry dos Santos; Maria Helena Kraeski; Thiago Sousa Matias; Anderson Simas Frutuoso (Universidade Federal de Santa Catarina, 2010)
Flexibility is one of the most important physical aspects in Rhythmic Gymnastics (RG). The purpose of the study was to compare long-term changes in flexibility of hip extension in athletes of RG in function of two techniques: the static stretch and Mulligan's Long Leg Traction. Participated eight female athletes with an average age of 13,25±0,89 years old, divided into two groups. Group 1 performed Mulligan technique and Group 2 performed static stretch. Flexibility training lasts for six weeks. It was executed 2 times a week, and was composed by 2 repetitions of 30 seconds for each lower limb. Photogrammetry was used to assess the range of motion (ROM) of hip extension. ROM was assessed before and after six weeks of training. Descriptive and inferential statistics were used to analyze the data. The increase of ROM was statistically significant in both lower limbs in Group 1, and in right lower limb (RLL) in Group 2. After six weeks of training the increase of ROM in Group 1 was 6,25°± 2,75º in left lower limb (LLL) and 5,25°± 2,63º in RLL, and the increase in Group 2 was 6,75º± 4,64º in LLL and 5,5º± 3,41º in RLL. Comparing the two executed techniques, in relation to the increase of ROM, there were no statistically significant differences. We conclude that after six weeks of training the two proposed techniques have showed increases in range of motion.